Multimodal Non-Surgical Treatments of Aggressive Pituitary Tumors - Nakano-Tateno, Tae; Lau, Kheng Joe; Wang, Justin; McMahon, Cailin; Kawakami, Yasuhiko; Tateno, Toru; Araki, Takako (Frontiers in Endocrinology, 2021)
Up to 35% of aggressive pituitary tumors recur and significantly affect mortality and quality of life. Management can be challenging and often requires multimodal treatments. Current treatment options, including surgery, conventional medical therapies such as dopamine agonists and somatostatin receptor agonists, and radiotherapy, often fail to inhibit pituitary tumor growth. Recently, anti-tumor effects of chemotherapeutic drugs such as Temozolomide, Capecitabine, and Everolimus, as well as peptide receptor radionuclide therapy on aggressive pituitary tumors have been increasingly reported with promising outcomes. The purpose of this review is to provide thorough information on non-surgical medical therapies and their efficacies and used protocols for aggressive refractory pituitary adenomas from pre-clinical level to clinical use.